Moderation and mediation analyses of exposure to television violence contents and contextual features and its influence on adolescents’ aggressive behaviours / Mohammad Yaakob - Yaakob, Mohammad (Institute of Graduate Studies, UiTM, 2012)
Previous studies on the effects of exposure to television violence on viewers’ aggressive behaviours have produced mixed results. Some studies have found significant effect sizes while others have found low and non-significant effect sizes. Television effects scholars have postulated that these mixed results are caused by the inconsistencies of research methodology employed and the inability to control major mediator variables in the studies. The present study is designed with the objectives to overcome these shortcomings.